ANTHONY COCCIOLO, Moving Image and Sound Collections for Archivists - Cohen-Palacios, Katrina (Archivaria, 2020)
Moving Image and Sound Collections for Archivists. Anthony Cocciolo. Chicago: Society of American Archivists, 2017. 218 pp. ISBN 0931828937